BOOK REVIEW: The University in Development: Case Studies of Use-Oriented Research. (March 2014) - Turpin, Tim
DAVID COOPER (2011), The University in Development: Case Studies of Use-Oriented Research . Cape Town: HSRC Press. 390 pp. PB. AUD58.00.